B-cell activating factor (BAFF) and BAFF-R levels correlate with B-cell subset activation and redistribution in controlled human malaria infection - Scholzen, Anja (2014)
Characteristic features of Plasmodium falciparum malaria are polyclonal B-cell activation and an altered composition of the blood B-cell compartment, including expansion of CD21−CD27− atypical memory B-cells. B-cell activating factor (BAFF) is a key cytokine in B-cell homeostasis, but its potential contribution to the modulation of the blood B-cell pool during malaria remains elusive. In the controlled human malaria model (CHMI) in malaria-naïve Dutch volunteers, we therefore examined the dynamics of BAFF induction and B-cell subset activation and composition, to investigate whether these changes are linked to malaria-induced immune activation and in particular induction of BAFF. Alterations in B-cell composition after CHMI closely resembled those observed in endemic areas. We further found distinct kinetics of proliferation for individual B-cell subsets across all developmental stages. Proliferation peaked either immediately after blood-stage infection or at convalescence, and for most subsets was directly associated with the peak parasitemia. Concomitantly, plasma BAFF levels during CHMI were increased and correlated with membrane-expressed BAFF on monocytes and dendritic cells, as well as blood-stage parasitemia and parasite-induced IFNγ. Correlating with elevated plasma BAFF and IFNγ levels, IgD−CD38lowCD21−CD27− atypical B-cells showed the strongest proliferative response of all memory B-cell subsets. This provides unique evidence for a link between malaria-induced immune activation and temporary expansion of this B-cell subset. Finally, baseline BAFF-receptor levels prior to CHMI were predictive of subsequent changes in proportions of individual B-cell subsets. These findings suggest an important role of BAFF in facilitating B-cell subset proliferation and redistribution as a consequence of malaria-induced immune activation.